TOXICITY TEST OF Gracilaria sp. AGAINST Aspergillus niger van Tieghem AND THE PHYTOCHEMICAL ANALYSIS - Nevy Widya Pangestika; I Gede Putu Wirawan; I Ketut Suada (International Journal of Biosciences and Biotechnology, 2020)
The purpose of this study was to know the effectiveness of Gracilaria sp. ethanol extract to inhibit the growth of Aspergillus niger. The results showed that the ethanol extract of Gracilaria sp. was not effective to inhibit the growth of A. niger. The minimum inhibitory concentration test (MIC) was carried out using extracts with 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7 %, 0.8 %, 0.9%, 1%, 2% and 0% percentage. The MIC results showed that the minimum extract inhibiting A. niger was 0.8%. The results of the antifungal activity test showed that the ethanol extract of Gracilaria sp. was fungistatic against A. niger. On the third day incubation, the 4% extract inhibited the growth of fungi with an average diameter of 5 mm. The fungal colony test was carried out using extract with 0.5%, 1%, 2%, 4% and 0% concentration, and the results showed that extract with 4% concentration can inhibit fungi colony growth by 69%. Phytochemical analysis was conducted using the UV-Vis Spectrophotometry, and the results showed that the ethanol extract of Gracilaria sp. contained 366.33 mg/100g/GAE phenol, 2041.47 mg/100g flavonoids, and 3041.60 mg/100g/TAE tannins. Tannins are suspected to be the most dominant fungistatic compound with the largest amount.